Preferred Educational Leaders: Character and Skills - T. Kilag, Osias Kit; Pasigui, Ronnie E.; Malbas, Marsha H.; Manire, Ezekiel A.; Piala, Mercenisa C.; Araña, Andre Mari M.; Sasan, John Michael (PT. Antis International Publisher, 2024)
This research study explored the characteristics and skills that teachers believe are important for educational leaders. Using a qualitative research approach and a phenomenological design incorporating narrative analysis, the study analyzed the perspectives of 10 teachers in Toledo City on this topic. The findings revealed that effective communication skills, emotional intelligence, vision and strategic planning, and passion for education were the four main themes identified by the participants as crucial characteristics and skills of educational leaders. These findings provide insights into what teachers value in their leaders and what they believe is important for the improvement of the education system. The study highlights the need for educational leaders to possess a range of characteristics and skills in order to be successful in their role and improve the learning experiences of their students.